2022
DOI: 10.1172/jci.insight.146374
|View full text |Cite
|
Sign up to set email alerts
|

Snapshots of nascent RNA reveal cell- and stimulus-specific responses to acute kidney injury

Abstract: The current strategy to detect acute injury of kidney tubular cells relies on changes in serum levels of creatinine. Yet serum creatinine (sCr) is a marker of both functional and pathological processes and does not adequately assay tubular injury. In addition, sCr may require days to reach diagnostic thresholds, yet tubular cells respond with programs of damage and repair within minutes or hours. To detect acute responses to clinically relevant stimuli, we created Rosa26-floxed-stop uracil phosphoribosyltransf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 95 publications
0
1
0
Order By: Relevance
“…Third, the pathogenesis is complex and, although preclinical studies utilizing various animal models may be useful, it also introduces additional complexities. When examining activated gene sets from a mouse model of prerenal and intrinsic AKI, functionally unrelated signal transduction pathways were identified and were localized in different cell types in the kidney (183,184). Compared with AKI with nonseptic etiologies, the pathophysiology of sepsis-associated AKI is complex; microarray studies using various rodent models of AKI showed that the LPS-induced sepsis-associated AKI had the largest number of uniquely altered genes compared with nonseptic AKI (185).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the pathogenesis is complex and, although preclinical studies utilizing various animal models may be useful, it also introduces additional complexities. When examining activated gene sets from a mouse model of prerenal and intrinsic AKI, functionally unrelated signal transduction pathways were identified and were localized in different cell types in the kidney (183,184). Compared with AKI with nonseptic etiologies, the pathophysiology of sepsis-associated AKI is complex; microarray studies using various rodent models of AKI showed that the LPS-induced sepsis-associated AKI had the largest number of uniquely altered genes compared with nonseptic AKI (185).…”
Section: Discussionmentioning
confidence: 99%